Optimization of aqueous extraction process for B-Glucosidase inhibitory componds from selected Malaysian herbs - Ahmad Barkat, Anumsima (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Diabetes is one of the chronic diseases affecting worldwide population. Presently, there is a growing interest in herbal remedies due to the side effects associated with the use of insulin and oral hypoglycaemic agents for diabetic patient. Therefore an investigation is required in a bionetwork rich and industrially-developed country like Malaysia to use alternative approaches to treat diabetics, such as plant based medicine. In this study, forty types of Malaysian anti-diabetic plants were examined on the basis of their use in traditional medicines throughout Southeast Asia, to develop an understanding of the distribution and to give an assessment of the diversity present in the selected plants. Total phenolic content of each medicinal plant also being analyzed by Folin and Ciocalteau's phenol reagent and their concentration was expressed as Gallic acid equivalent (GAE). The results indicated that all plant samples gave positive results with varying concentrations except for Asystasia gangetica. Highest amount of phenolic content was obtained from Piper betle L., which has phenolic concentration of 9320.0 mg/l GAE, while the lowest concentration of 35.0 mg/l GAE was obtained from Crinum asiaticum L. Extracts of all forty species of Malaysian medicinal plants were examined for β-glucosidase inhibition using an in-vitro model. Most of the plants showed varying degree of inhibitory activity (%) but Centella asiatica had the maximum percentage of β-glucosidase inhibitory activity (99.03%) while the second best was Morinda citrifolia with 96.37% inhibitory activity. Another two potential plants which gave higher inhibitory activity were Cucumis sativus (93.95%) and Euphorbia tircalli L. (90.56%). Methanol was determined as the best solvent to extract β-glucosidase inhibitor from medicinal plants because all the four selected plants gave the high level of inhibition activity in methanol extract. Hexane, dichloromethane and distilled water were also found to have potential to extract diabetic inhibitor. However for optimization purpose, distilled water was chosen to be the main solvent for extraction and Cucumis sativus as the potential plant. Through optimization it was observed that β-glucosidase inhibitory activity reached the highest value of 96.81% at the optimum conditions of temperature, 25.66 C; incubation time, 22.30 hours; agitation speed, 125 rpm and volume of solvent, 15.6 ml. High Performance Liquid Chromatography (HPLC) analysis identified five compounds, out of which three were identified as p-coumaric acid, syringic acid and ferullic acid while the other two were unknown. These two known phenolic acids already known to have anti-diabetic properties from previous study. But it is still uncertain which compound gave positive response to β-glucosidase inhibition assay. Further analysis should be done in the future to determine the exact amount of compound, which can inhibit β- glucosidases activity. These potential plants with β-glucosidase inhibitory activity can be a hope for millions for treatment of diabetes and will also help in reducing the dependence on synthetic drugs in the future. Recent studies by other researchers also showed that these phytochemicals have certain therapeutic properties.